2016
DOI: 10.1038/srep36152
|View full text |Cite
|
Sign up to set email alerts
|

Homophily in coauthorship networks of East European sociologists

Abstract: We study to what degree and how homophily and network properties affect individual citation counts of researchers in the sociology departments of three East European countries, namely Poland, Romania, and Slovenia. We built first-order personal coauthorship networks out of the Web of Science publication records. Each sociologist is assigned as a focal node or ego, while her coauthors are alters. We analyze the data using structural measurements methods, hierarchical regression models, and we make visualization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…International collaborations are increasingly possible and encouraged, e.g., within Horizon 2020 and Biodiversa-EraNet project partnerships (Granieri and Renda 2012). These collaborations can allow knowledge flow, the development of new coauthorship networks (Hancean and Perc 2016) and also can buffer the unstable funding which characterizes Romanian research (Miclaus and Micu 2018). Our results suggest several ways in which a local researcher can increase its attractivity for international research projects, including a keen interest in a holistic understanding of the cultural landscapes (of which grasslands are part), active and long-term engagement with local stakeholders and partners and increased scientific productivity (Balvanera et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…International collaborations are increasingly possible and encouraged, e.g., within Horizon 2020 and Biodiversa-EraNet project partnerships (Granieri and Renda 2012). These collaborations can allow knowledge flow, the development of new coauthorship networks (Hancean and Perc 2016) and also can buffer the unstable funding which characterizes Romanian research (Miclaus and Micu 2018). Our results suggest several ways in which a local researcher can increase its attractivity for international research projects, including a keen interest in a holistic understanding of the cultural landscapes (of which grasslands are part), active and long-term engagement with local stakeholders and partners and increased scientific productivity (Balvanera et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the network fragmentation metric, which in our case indicates the proportion of pairs of authors that cannot reach each other (Borgatti et al 2018). Large datasets, as it is the case of our database, typically involve many small independent clusters around larger ones and one large and dense cluster (Hancean and Perc 2016). Thus, we assessed the distribution of components in the co-authorship network and extracted the largest connected component (main component) that shows the group of highly active authors focused on grasslands at the national level (subnetworks of authors that are maximally connected between each other).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Karlovčec et al (2016) used machine learning approach to study the transition behaviour of researchers between core and periphery in the Slovenian research network. Hâncean and Perc (2016) studied how different network properties affect citation counts of sociologists of East European countries including Slovenia. Results indicated that the score of the citations of a researcher could be clearly predicted by the citation counts of her co-authors.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, and in line with the findings of Plümper [33] as outlined above, political science institutes vary strongly in their international visibility. In the neighboring discipline of sociology, co-authorship networks were recently investigated in Romania [39] as well as in Poland, Romania and Slovenia [40]. …”
Section: Previous Research On the Structure Of German Political Sciencementioning
confidence: 99%